Original articleThe effect of basic neuropsychological interventions on performance of students with dyscalculia - Faramarzi, Salar; Sadri, Sima (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2014)
Objective : There are many children who have dyscalculia. The aim of the current research was to investigate the effectiveness of basic neuropsychological interventions in improving mathematics performance of girl students (8-9 years old) with dyscalculia (mathematics learning disabilities) in Isfahan city of Iran. Material and methods : The research method was experimental with pretest, posttest and a control group. To this end, the statistical population of this study comprised second grade girl students (8-9 years old) of elementary school during 2011-2012. Considering the entry requirements for the research, 30 girl students were selected by multi-stage sampling and were randomly assigned to two groups, experimental and control. To gather data, the Wechsler Intelligence Scale for children (WISC-III-R), Keymath test, math academic performance test and clinical interview were used. The obtained data were analyzed by covariance analysis and using SPSS18 statistical software. Results: The results revealed a significant difference between the mathematics performance of the experimental and control groups, girl students with dyscalculia, in pretest and posttest stages with p ≤ 0.001 significance level. Conclusions: According to the results of the research, it is suggested that neuropsychological interventions can improve mathematics performance of students with dyscalculia and this method can be used for curing and assisting this group of students.